Identifying and Overcoming Perceived Barriers of Providers towards HPV Vaccination: A Literature Review. (10th December 2015) - Palmer, Jessica; Carrico, Catherine; Costanzo, Cindy
Abstract : Human papillomavirus (HPV) is a common sexually transmitted infection in the United States associated with nearly 26, 000 cases of cancer annually. With the recent addition of Gardasil 9, three vaccines are now licensed by the Food and Drug Administration (FDA) and recommended by the Advisory Committee on Immunization Practices (ACIP) for HPV prevention. While providers are the preferred source in educating individuals on HPV and HPV vaccination, low uptake percentages indicate that providers are missing valuable opportunities to educate and strongly recommend HPV vaccination. It is critical to examine perceived barriers and attitudes among providers related to HPV and HPV vaccination to identify factors that influence vaccination coverage. This paper aims to expand provider knowledge and awareness of factors that may facilitate an increase in HPV vaccination coverage and subsequent cancer prevention.